Mapping the Potential and Challenges of Developing the Waru Brilliant Thematic Village in Bojong Renged - Megantara Pura; Simon Petrus Wenehenubun; Rahmi Andarini; Fahmy Rinanda Saputri (I-Com: Indonesian Community Journal, 2025)
The Waru Brilliant Thematic Village in Bojong Renged has been developed since 2021 in response to the limited natural resources in the Tangerang region and the impact of the COVID-19 pandemic. This program utilizes idle land for integrated agricultural and livestock activities, such as melon greenhouses, mushroom cultivation, chili gardens, and fish spawning. This service activity aims to map the available potential and identify the main challenges that hinder sustainability. Implementation methods include field observations, interviews with residents, and documentation of facilities. The results show that the physical potential is quite large but has not been supported by sustainable management. The main problems lie in low community participation, damage to facilities due to lack of ownership, and technical constraints related to weather and crop distribution. The findings emphasize the importance of collaboration and technology-based community empowerment strategies to support the sustainability of thematic villages.